Ḥāshiyat al-Bājūrī ʻalá matn al-Burdah - Bājūrī, Ibrāhīm ibn Muḥammad, 1783 or4-1860 (Mawlawī Muḥammad ibn Ghulām Rasūl al-Sūratī, 1982)
Commentary on Burdah al-madīḥ, classical Arabic poetical work honoring prophet Muhammad, by Būṣīrī, 1213?-1296?